Lung Ultrasonography and Chest Radiography in Suspected Cases of Pneumonia in Critically Ill Patients- A Comparative Study - Bharat M.P; Deepak K.S (Asian Journal of Medical Radiological Research, 2020)
Background: The present study compared lung ultrasound (USG) and chest radiography in suspected cases of pneumonia in critically ill patients. Subjects & Methods: 56 patients age above 20 years of age of both genders diagnosed with pneumonia were included. Patients were subjected to chest USG and X ray. Positive predictive values for both lung ultrasound and chest X-ray were calculated. Results: Age group 20-30 years had 4 patients, 30-40 years had 6, 40-50years had 10, 50-60 years had 16 and >60 years had 20 patients. The difference was significant (P< 0.05). Chest x ray reveled 40 out of 56 cases positive and 16 negative and USH showed 52 positive and 4 negative. Positive predictive value (PPV) of chest x- ray was 71.4% and USG was 92.8%. The difference was significant (P< 0.05). Conclusion: Lung ultrasound is an effective radiological tool for the assessment of suspected cases of pneumonia as compared to chest x ray.